TAFSIR BIL ISYARI DAN KITAB TAFSIR BIL ISYARI SERTA PENAFSIRANNYA - Irpan Hadi; Agus Rifqi Ridwan (Lughoti (Jurnal Pendidikan Bahasa Arab) Jurnal program studi PBA, 2024)
The different interpretations of the Qur'an according to the Zahir verse are because there are implicit instructions and are only known by some scholars, or only known by people who know Allah, namely people who have noble personalities and have trained their souls (mujahadah) and those who are given light. by Allah so that they can reach the secrets of the Qur'an, their minds are full of deep meanings through divine inspiration or Allah's help, so that they can combine the implied understanding with the explicit meaning of the verses of the Al-Qur'an in an effort to interpret The verses of the Qur'an are not with their zahir meaning but rather with the voice of conscience, after previously interpreting the zahir meaning of the verse in question. ulama, or only known by people who know Allah, namely people who have noble personalities and have trained their souls (mujahadah). The interpretation of this Isyari if it enters into vague hints will be a mistake, but as long as it is a good Istinbat and in accordance with what is indicated by Arabic language and supported by evidence of its authenticity, without contradiction, then it can be accepted. Background to the emergence of Tafsir Al-Isyari. The development of Sufism which is increasingly widespread in the Islamic world, is marked by the practices of asceticism and ascapism carried out by the early generations of Islam, this Starting from the emergence of political conflict after the death of the Prophet Muhammad SAW, practices like this continued to develop in the following period. Keywords : Tafsir Bil Isyari, kitab tafsir Bil Isyari, Penafsiran Tafsir Bil Isyari